(3QehR GdUMGaI(B- (3QehR GdSjGSI h gehe CNQi (B/s - (3fUGQ, YHO Gddgs ((3GScfOQjI (B:s (3OGQ GdhaGA dOfjG GdWHGYI h GdfTQ ,s, 2000)
(3gPG GdcJGH jLeY Hjf GdGeJfGY GdHGdZ h GdYeb GdTOjO jbOe dc GdOcJhQ fUGQ YHO Gddg QDjJg GdNGUI dYOO ef GHQR QehR GdUMGaI h GdGYdGe aj eUQ h GdYGde GdYQHj Vef eG jbOeg dc ef gehe GNQi JVefJgG eLehYI eNJGQI ef GHQR ebGdGJg cGf dgG dOi fTQgG QO aYd bhj eGRGdJ GUOGDg JJQOO Gdi GdGfs
Keywords: (3Ydhe SjGSjIs; (3GdUMGaIs